2019
DOI: 10.1002/da.22986
|View full text |Cite
|
Sign up to set email alerts
|

Joint and dose‐dependent associations between aerobic and muscle‐strengthening activity with depression: A cross‐sectional study of 1.48 million adults between 2011 and 2017

Abstract: Background: Research has shown that regular physical activity is key for the prevention and/or treatment of depression. However, epidemiological studies describing the associations between different physical activity modes (i.e., aerobic vs. muscle-strengthening exercise) with depression are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
3
26
2
Order By: Relevance
“…In addition to these independent health benefits, our recent epidemiological studies suggest that, compared to engaging in either the muscle-strengthening exercise guideline (≥ 2 sessions/week) or the aerobic MVPA guideline alone (≥ 150 min/week), the combination of both (as is prescribed in the current guideline) may be most beneficial for the prevention and/or management of multiple prevalent chronic health conditions [14,49,[53][54][55][56][57][58]. Our cross-sectional studies, amongst large samples (range:~10,000 to~1.7 million adults) across several countries (e.g.…”
Section: Run Lift or Both?-emerging Epidemiological Evidence For Commentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these independent health benefits, our recent epidemiological studies suggest that, compared to engaging in either the muscle-strengthening exercise guideline (≥ 2 sessions/week) or the aerobic MVPA guideline alone (≥ 150 min/week), the combination of both (as is prescribed in the current guideline) may be most beneficial for the prevention and/or management of multiple prevalent chronic health conditions [14,49,[53][54][55][56][57][58]. Our cross-sectional studies, amongst large samples (range:~10,000 to~1.7 million adults) across several countries (e.g.…”
Section: Run Lift or Both?-emerging Epidemiological Evidence For Commentioning
confidence: 99%
“…the USA, Germany and South Korea) have shown that compared to meeting the aerobic MVPA or muscle-strengthening exercise guideline alone, meeting both guidelines was associated with several important indicators of health. These include a reduced prevalence of cardiometabolic (hypertension, diabetes, cardiovascular disease) and general health conditions (arthritis, chronic obstructive pulmonary disease, asthma) [54,58]; depression/depressive symptom severity [53,56,57]; obesity [49]; and prevalence of hyperglycaemia and dyslipidaemia [55]. Given the cross-sectional nature of these data, we urge caution in drawing strong causal inferences.…”
Section: Run Lift or Both?-emerging Epidemiological Evidence For Commentioning
confidence: 99%
“…16 Further, both aerobic MVPA and MSE are associated with improved depression and anxiety symptoms, [41][42][43] which are also associated with sleep, and some evidence exists of added mental health benefits to these outcomes when engaging in both aerobic MVPA and MSE. 17,19,44 To further establish how combined MVPA-MSE is related to sleep health, it is recommend that future experimental studies are encouraged to compare the effects of discrete grouping of physical activity modes (ie, control vs aerobic MVPA vs MSE vs combined aerobic MVPA-MSE) on components of sleep health, and also examine cardiometabolic and mental health as potential mediators of change.…”
Section: Discussionmentioning
confidence: 99%
“…20 Body mass index (BMI) was calculated from self-reported height (meters) and weight (kilograms) using the formula: BMI = kg/m 2 . In addition, since poor mental health can negatively impact on both physical activity 17,30 and sleep, 32 we also adjusted for a proxy assessment of depression, classified as previous clinical diagnosis for depression. Last, we adjusted for the selfreported presence ("yes," "no" to each comorbidity) of the following comorbidities: arthritis/rheumatoid arthritis, hypertension, asthma, diabetes, high cholesterol, myocardial infarction, coronary heart disease, stroke, chronic obstructive pulmonary disease, kidney disease, and cancer (nonskin).…”
Section: Observed Snoring and Observed Stopped Breathing During Sleepmentioning
confidence: 99%
See 1 more Smart Citation